Diplomacia solidária em saúde global: estratégias políticas que criam normas jurídicas? - Costa, José Guilherme Ferraz da (2019)
The present work starts with the construction of a concept of solidarity diplomacy in global health, encompassing initiatives of official assistance to the development focused on the guarantee of public health services marked by a more intense note of solidarity, as theoretical reference to study the case of two large strategies implemented throughout the first decades of XXI Century. Such strategies consist of the international campaign for access to medicines and the intensification of South-South cooperation initiatives in health, which reveal the characteristics of the theoretical model of solidarity diplomacy, such as: a) concessions with no counterparts required; b) systematic structural planning; c) participation of civil society; and d) recognition of the right to health. The same strategies have resulted in the capitalization of international recognition and prestige for Brazil, for the notable promotion of access to health services and inputs by vulnerable populations around the world. In addition, they have resulted in a sensitive contribution to the process of formation of norms that convey or reinforce extraterritorial obligations to respect, protect and satisfy (in the modalities of facilitating, promoting and providing), through the mechanisms of normative irradiation of the human rights regime and sedimentation of the elements constitutive of customary rules in international law.